2013
DOI: 10.1007/s00432-013-1523-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index predicts outcomes of malignant pleural mesothelioma

Abstract: Pretreatment PNI is a novel independent prognostic factor in MPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 27 publications
5
45
1
Order By: Relevance
“…NLR may present the pro-angiogenic/pro-inflammatory status in tumor tissue [10], and may also show how to balance neutrophils and lymphocytes, and then reflect patients' immune function [11, 12]. Preclinical studies showed that neutrophils may act through TGF-β induced signal pathway, with tumor promoting proliferation of leucocytes [13]. Patients with an elevated NLR exhibit the ratio of neutrophils and lymphocytes and may indirectly suggests poorer lymphocyte-mediated immune response to tumors, therefore, accelerating the process of tumor and prompting with worse prognosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…NLR may present the pro-angiogenic/pro-inflammatory status in tumor tissue [10], and may also show how to balance neutrophils and lymphocytes, and then reflect patients' immune function [11, 12]. Preclinical studies showed that neutrophils may act through TGF-β induced signal pathway, with tumor promoting proliferation of leucocytes [13]. Patients with an elevated NLR exhibit the ratio of neutrophils and lymphocytes and may indirectly suggests poorer lymphocyte-mediated immune response to tumors, therefore, accelerating the process of tumor and prompting with worse prognosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Identifying prognostic factors before surgery to help determine the optimal preoperative therapy and timing of surgery is important. Previous attempts have focused on a number of immuno-nutritional indices, including PNI, NLR, PLR, PI, and GPS [4,6,7,9,15,21,[25][26][27] . However, their reported prognostic value can vary between studies of the same cancer type; for example, in hepatocellular carcinoma, PLR was found to be a prognostic marker in one study, but another study suggested that only PNI was a prognostic marker [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Mohri et al [7] demonstrated that preoperative PNI is a useful predictor of postoperative complications and survival in patients with colorectal cancer. Yao et al [19] showed that PNI, an indicator of nutritional status that is simple to construct from laboratory parameters, is a useful predictor of the long-term outcome of malignant pleural mesothelioma. However, the optimal cutoff value of the PNI to predict the long-term outcomes remains unclear.…”
Section: Table 3 Univariate and Multivariate Cox Regression Analyses mentioning
confidence: 99%